RANCANG BANGUN SISTEM PENGUKUR INTENSITAS CAHAYA MENGGUNAKAN MICROSOFT VISUAL STUDIO C# UNTUK MENENTUKAN SUDUT PUTAR JENIS LARUTAN GULA - Wardono Istiyawan; K. Sofjan Firdausi; Heri Sugito (Youngster Physics Journal, 2012)
A system of measuring the light intensity to determine the specific rotary angle of  sugar has been carried out. Research is done using a computer with a Microsoft Visual Studio C#. In this research there are some stages as follow light sensors and the system of measuring polarization angle. LDR as light intensity sensor, the result has been processed in a series of conditioning at the output signal. The result of  this series can be input in interface application.  Measurement of polarization angle can be done by counting average value of the intensity before it gets into the materials and thereafter. This system has been realized and can show the results obtained in the form of graphs and can be stored. The value of the angular turn kinds of sugar unmeasured is (51,33±0,42) omL/dm gram. Results of testing equipment and the characteristics of the sensor with a linear regression coefficient R2 = 0,9906 and  SD = 0,82. Keyword : Microsoft Visual Studio C#, Specific rotary angle, Polarization angle,  LDR